Prognosis, Early Diagnosis and Treatment of Multiple Organ Failure in a Patient With Severe Concomitant Trauma - E. S. Vladimirova; P. A. Ivanov; S. A. Badigov; I. E. Popova; S. I. Rey; O. A. Alekseechkina; G. A. Berdnikov; E. A. Tarabrin (Неотложная медицинская помощь)
On the example of a clinical observation, we demonstrate the possibilities of dynamic multimodality imaging techniques and clinical and laboratory data, taking into account the severity of the concomitant trauma, which allow us to reflect objectively the dynamics of post-traumatic changes in the organs and tissues and predict the course of multiple organ failure (MOF). Consistency and adequate choice of treatment tactics with early use of active detoxification methods contribute to a favorable outcome.